Seroprevalence of NMO-IgG antibody in Brazilian patients with neuromyelitis optica Soroprevalência do anticorpo NMO-IgG em pacientes brasileiros com neuromielite óptica - Tarso Adoni; Angelina Maria Martins Lino; Paulo Eurípedes Marchiori; Fernando Kok; Dagoberto Callegaro (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To determine the seroprevalence of neuromyelitis optica antibody (NMO)-IgG in Brazilian patients with clinical diagnosis of relapsing neuromyelitis optica, also known as Devic's disease. METHOD: We determined NMO-IgG titers in 28 patients (25 of them females) that fulfilled the 1999 NMO diagnostic criteria proposed by Wingerchuk et al. RESULTS: NMO-IgG was detected in 18 NMO patients (64.3%). CONCLUSION: Our results showed that seroprevalence of NMO-IgG in Brazilian NMO patients was similar to the observed in other studies. OBJETIVO: Determinar a soroprevalência do anticorpo neuromielite óptica (NMO)-IgG em pacientes brasileiros com diagnóstico de neuromielite óptica recorrente, também conhecida como doença de Devic. MÉTODO: Nós pesquisamos a presença do anticorpo NMO-IgG em 28 pacientes (25 do sexo feminino) que preenchiam os critérios diagnósticos para NMO propostos por Wingerchuk et al. em 1999. RESULTADOS: Dezoito pacientes (64,3%) apresentaram a pesquisa positiva do NMO-IgG. CONCLUSÃO: Nossos resultados demonstraram que a soroprevalência do anticorpo NMO-IgG em pacientes brasileiros com NMO é semelhante àquela encontrada em outros estudos.